The effect of irrigation with drainage water on some chemical soil properties and the yield of different field crops - El Guindy S.; El Nasser G.A.; Abu-Bakr A.; El Sissi L. (Reuse of low quality water for irrigation, 1989)
To carry out this study, an experimental area of 2.5 fedd. was established in Fayoum Governorate (Egypt) where drainage, mixed and fresh water have been used for irrigation of common crops in the Fayoum area. Data concerning soil and crops were collected frequently and analysed. This paper presents the results of the effect of irrigation water quality on some chemical soil properties and the productivity of some field crops.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)